1978
DOI: 10.1177/036354657800600609
|View full text |Cite
|
Sign up to set email alerts
|

Patellar tendinitis (jumper's knee)

Abstract: A jumper's knee is an overload lesion of patellar or quadriceps tendon near its insertion at the lower or upper pole of the patella. If conservative treatment fails, an operation can be performed in Phase 3 where disabling symptoms, are present. The necrotic tissue in the patellar tendon is excised. The early results of this surgery are encouraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
1
17

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(127 citation statements)
references
References 3 publications
1
108
1
17
Order By: Relevance
“…A number of authors have described open surgical techniques to treat patients unresponsive to nonoperative treatment [2,4,6,9,11,14] to partially remove the patellar tendon, open the peritenon, and remove or drill the patellar pole. More recently, arthroscopically assisted procedures [3,8,12] have been reported that focus on tendon débri-dement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of authors have described open surgical techniques to treat patients unresponsive to nonoperative treatment [2,4,6,9,11,14] to partially remove the patellar tendon, open the peritenon, and remove or drill the patellar pole. More recently, arthroscopically assisted procedures [3,8,12] have been reported that focus on tendon débri-dement.…”
Section: Discussionmentioning
confidence: 99%
“…A number of papers describe open surgical techniques to treat patients unresponsive to nonoperative treatment [2,5,6,9,11,14] to partially remove the patellar tendon, open the peritenon, and remove or drill the patellar pole. These techniques reportedly relieve pain and restore function in 60% to 100% of patients [3,5,6,14].…”
Section: Introductionmentioning
confidence: 99%
“…Classificação -A classificação de Blazina pode ser usada na tendinopatia patelar (31) . Roels et al modificaram a classificação de Blazina (32) . Essa classificação divide a dor em quatro graus: grau I -dor leve após atividade física; grau II -dor no início da atividade física, melhora após o aquecimento, piora no final do exercício, sem diminuição do rendimento; grau IIIdor durante e após a atividade física com piora importante do rendimento do atleta; grau IV -ruptura parcial ou total do tendão.…”
Section: Avaliação Clínicaunclassified
“…Physical data (body weight and height) were also collected using a questionnaire, and Roel's stages were used to categorize the degree of severity of jumper's knee and knee contusions 4) .…”
Section: Methodsmentioning
confidence: 99%